Poverty Reduction Strategies for Sustainable Economic Growth: Implications for Women's Empowerment in Nigeria (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2026)
This paper examines the interplay between poverty reduction strategies, sustainable economic growth, and women's empowerment in Nigeria. Despite Nigeria's cultural diversity and economic potential, the nation grapples with entrenched poverty that disproportionately affects women. Research from the Nigerian Institute of Social and Economic Research (NISER, 2020) underscores women's heightened vulnerability to poverty, stemming from factors like limited land ownership and constrained access to credit. The paper addresses the problem of gender disparities exacerbated by the absence of policies tailored to women's unique challenges. It underscores the need for gender equity, not only for social justice but as a practical necessity for fostering sustainable economic growth. The paper employs a multidimensional approach, drawing from existing research, policy frameworks, and theoretical perspectives including feminist theory, intersectionality theory, and empowerment theory. Key findings emphasize the potential advantages of gender-integrated poverty reduction strategies, including increased economic growth, reduced poverty, improved human capital development, and enhanced gender equality. The paper also highlights challenges such as entrenched gender norms and difficulties in targeting vulnerable populations. The paper concludes by underscoring the importance of integrating gender considerations into poverty reduction strategies, recommending gender mainstreaming in policies to promote women's economic participation and rights. The significance of this research lies in its potential to inform policy decisions and promote women's empowerment in Nigeria, aligning with the United Nations Sustainable Development Goals.